Local monitoring of airborn technogenic pollution in the area of metallurgical plants of «Arcelor Mittal» company - Харитонов, М. М.; Бенселгуб, А.; Криваковська, Р. В. (Scientific Progress & Innovations, 2017)
The application of local monitoring based on automatic weather monitoring networks data, allows assessing pollution risks near metallurgical plants of «Arselor Mittal» company. Two zones of air pollution with nitrogen dioxide in the level of 1 MPC has been recorded near the blast furnaces and the steel complex in city Annaba. It shows that in general the values ​​are not alarming. They are all and across all measurement sites below the WHO limit value of 30 mg/m3 per year to 1,5 times. The concentration of the cloud increased concentration of nitrogen dioxide in close proximity to the neighbouring residential districts of Sidi-Amar and El-Hajjar is also a concern. According to the majority data obtained from stationary monitoring stations, the annual average concentration of SO2 was significantly lower than the MPC. However, a twofold excess of MPC was found in the complex hot zone (sintering and melting of iron ore in the blast furnace). This is due to the fact that during the coking process of coal there is a strong release of sulfur originally contained in the coal lane. On the other hand, the zone blast furnace plays the role of purifying the melting of its undesirable elements in the steel. Mainly the sulfur is released during cooling. Monitoring data show the danger of the spread of organic pollutants beyond the factory area. Up to 30 % of the results of all the sites monitored, exceeded the WHO guideline value. The highest concentration of benzene and toluene recorded in the coking area in February – March. High concentration of toluene and benzene were observed near post installed in suburb district Sidi Amar. The situation on air pollution with nitrogen and sulfur dioxide in city Kryvyi Rih is sufficient contrast. Many point sources individual emissions overlay and form the total torch, which cover all agglomeration.